THE ASSESSMENT OF DIFFICULTY OF YACHT SAILING CLASSES AND STUDENTS' GLOBAL SELF-ESTEEM - Anna Romanowska-Tolloczko; Piotr Piwowarczyk (Physical Education of Students, 2015)
Purpose: determination of relationship between the level of students’ global self-esteem and their perception of the degree of difficulty sailing yacht classes. Material and methods: Study consisted of 178 students of University School of Physical Education in Wrocław. The study used two tools: Polish adaptation of SES M. Rosenberg Self-Esteem Scale and a questionnaire designed by the authors of the study. Results: men were characterized by a higher self-esteem than women. Distribution of the results obtained by women was closer to a normal distribution, but it was not completely compatible with it. The relationship was noted between the level of global self-esteem of the students and their perception of the degree of difficulty of the course. People with higher self-esteem assessed the knowledge and skills of sailing as easier. For people with lower levels of self-esteem sailing it was a more difficult. Conclusions: self-acceptance and self-esteem have a substantial impact on goal setting and the perception and taking various tasks. It is therefore important to help young people to build adequate self-esteem and positive self-image, because faith in its own strength and capabilities is a key element in achieving success in every area of life.